The Evolution of Public Health Genomics: Exploring Its Past, Present, and Future - Molster, Caron M.; Bowman, Faye L.; Bilkey, Gemma A.; Cho, Angela S.; Burns, Belinda L.; Nowak, Kristen J.; Dawkins, Hugh J. S. (Frontiers in Public Health, 2018)
Public health genomics has evolved to responsibly integrate advancements in genomics into the fields of personalized medicine and public health. Appropriate, effective and sustainable integration of genomics into healthcare requires an organised approach. This paper outlines the history that led to the emergence of public health genomics as a distinguishable field. In addition, a range of activities are described that illustrate how genomics can be incorporated into public health practice. Finally, it presents the evolution of public health genomics into the new era of ‘precision public health’.